Waqfs Partnership with the Public and Private Sectors in the Kingdom of Saudi Arabia (مجلة وقف في دراسات الاوقاف, 2026)
Supervisor of the General Administration of Waqfs and Investments at the Islamic UniversityOrigin of the book: A thesis submitted to obtain a doctorate degree from the Department of Islamic Economics at the Faculty of Sharia at the Islamic University of Madinah  The research problem was a central question, which is:How can the partnership between the public and private sectors be an effective tool in the field of Waqf, effectively contributing to a qualitative shift for the Waqf, and maximizing its development and financing impact?The study was based on a main hypothesis, which is the advancement of the Waqf sector in the Kingdom of Saudi Arabia, so that it can effectively carry out development and financing, which requires the establishment of a smart partnership between the public sector and the private sector. The study used the descriptive, analytical and inductive approach. The study proved, through its analysis of the performance of the applied models in question, the validity of the main hypothesis on which it was based.The study was organized into an introductory chapter and six chapters.The introductory chapter dealt with:The conceptual framework of the subjects of the study.The first chapter dealt with:The reality of Waqfs in the Kingdom of Saudi Arabia.The second chapter dealt with:Public-Private Partnership through Namaa Al Munawarah.The third chapter dealt with:The economic and developmental impact of endowing Namaa Al-Munawarah through the results of its implemented programs.The fourth chapter dealt with:Talking about the partnership between the public and private sectors through the Awqaf of the Islamic University of Madinah.The fifth chapter dealt with:The partnership between the public and private sectors through the Awqaf of the General Presidency for the Affairs of the Two Holy Mosques.The sixth chapter dealt with:The study's findings and recommendations.